Vitamin D Enhances Anticancer Properties of Cediranib, a VEGFR Inhibitor, by Modulation of VEGFR2 Expression in Melanoma Cells - Piotrowska, Anna; Beserra, Fernando Pereira; Wierzbicka, Justyna Marta; Nowak, Joanna Irena; Żmijewski, Michał Aleksander (Frontiers in Oncology, 2021)
Regardless of the recent decade pathbreaking introduction of personalized therapy, melanoma continuously represents one of the most lethal skin malignancies. Still, a substantial proportion of patients either fail to respond to the therapy or will relapse over time, representing a challenging clinical problem. Recently we have shown, that vitamin D enhances the effectiveness of classical chemotherapeutics in human malignant melanoma A375 cell line. In search for new combination strategies and adjuvant settings to improve melanoma patients outcomes in the current study the effects of cediranib (AZD2171), an oral tyrosine kinase inhibitor of VEGFR1-3, PDGFR, and c-KIT, used in combination either with 1,25(OH)2D3 or with low-calcemic analog calcipotriol, were tested on four human malignant melanoma cell lines (A375, MNT-1, RPMI-7951 and SK-MEL-28). Melanoma cells were pretreated with vitamin D and subsequently exposed to cediranib. We observed a marked decrease in melanoma cell proliferation (A375 and SK-MEL-28), G2/M cell cycle arrest and a significant decrease in melanoma cell mobility in experimental conditions used (A375). Surprisingly, concurrently with very desirable decrease in melanoma cell proliferation and mobility we noticed the up-regulation of VEGFR2 at both, protein and mRNA levels. No effect of vitamin D was observed in MNT-1 and RPMI-7951 melanoma cells. It seems, that vitamin D derivatives enhance cediranib efficacy by modulation of VEGFR2 expression in melanoma cells experessing VEGFR2. Concluding, our experiments demonstrated that vitamin D derivatives are very promising candidates as novel adjuvants to conquer melanoma, especially in patient suffering from vitamin D defficiency. However, further extensive research is indispensable to reliably assess their potential benefits for melanoma patients.